Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the equations of the straight lines passing through the point of intersection of the lines [tex]\(2x - 3y + 1 = 0\)[/tex] and [tex]\(x + y - 2 = 0\)[/tex] that make an angle of [tex]\(45^\circ\)[/tex] with the line [tex]\(x + 2y - 5 = 0\)[/tex], we can proceed step-by-step as follows:
### Step 1: Find the Point of Intersection
First, we need to find the point of intersection of the lines [tex]\(2x - 3y + 1 = 0\)[/tex] and [tex]\(x + y - 2 = 0\)[/tex].
1. Solve the system of equations:
[tex]\[ x + y - 2 = 0 \][/tex]
[tex]\[ y = 2 - x \][/tex]
2. Substitute [tex]\( y = 2 - x \)[/tex] into [tex]\(2x - 3y + 1 = 0\)[/tex]:
[tex]\[ 2x - 3(2 - x) + 1 = 0 \][/tex]
[tex]\[ 2x - 6 + 3x + 1 = 0 \][/tex]
[tex]\[ 5x - 5 = 0 \][/tex]
[tex]\[ x = 1 \][/tex]
[tex]\[ y = 2 - 1 = 1 \][/tex]
Therefore, the point of intersection is [tex]\((1, 1)\)[/tex].
### Step 2: Determine the Slope of the Given Line
We need the slope of the line [tex]\(x + 2y - 5 = 0\)[/tex].
1. Rewrite the equation in slope-intercept form [tex]\(y = mx + c\)[/tex]:
[tex]\[ x + 2y - 5 = 0 \][/tex]
[tex]\[ 2y = -x + 5 \][/tex]
[tex]\[ y = -\frac{1}{2}x + \frac{5}{2} \][/tex]
Thus, the slope ([tex]\(m_2\)[/tex]) of the line [tex]\(x + 2y - 5 = 0\)[/tex] is [tex]\(-\frac{1}{2}\)[/tex].
### Step 3: Determine the Slopes of the Desired Lines
To find the lines making a [tex]\(45^\circ\)[/tex] angle with the slope [tex]\(m_2 = -\frac{1}{2}\)[/tex], we use the tangent formula for angles between two lines:
[tex]\[ \left| \frac{m_1 - m_2}{1 + m_1 m_2} \right| = \tan(45^\circ) = 1 \][/tex]
where [tex]\(m_1\)[/tex] is the slope of the desired line.
Substitute [tex]\(m_2 = -\frac{1}{2}\)[/tex]:
[tex]\[ \left| \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} \right| = 1 \][/tex]
This gives two cases:
[tex]\[ \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = 1 \][/tex]
[tex]\[ \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = -1 \][/tex]
Solve these equations separately:
1. First case ([tex]\( \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = 1 \)[/tex]):
[tex]\[ m_1 + \frac{1}{2} = 1 - \frac{1}{2}m_1 \][/tex]
[tex]\[ m_1 + \frac{1}{2}m_1 = 1 - \frac{1}{2} \][/tex]
[tex]\[ \frac{3}{2}m_1 = \frac{1}{2} \][/tex]
[tex]\[ m_1 = \frac{1}{3} \][/tex]
2. Second case ([tex]\( \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = -1 \)[/tex]):
[tex]\[ m_1 + \frac{1}{2} = - (1 - \frac{1}{2}m_1) \][/tex]
[tex]\[ m_1 + \frac{1}{2} = -1 + \frac{1}{2}m_1 \][/tex]
[tex]\[ m_1 - \frac{1}{2}m_1 = -1 - \frac{1}{2} \][/tex]
[tex]\[ \frac{1}{2}m_1 = -\frac{3}{2} \][/tex]
[tex]\[ m_1 = -3 \][/tex]
### Step 4: Equations of the Desired Lines
Using the point-slope form of the line equation, we can write the equations of the lines passing through [tex]\((1, 1)\)[/tex]:
1. For [tex]\(m_1 = \frac{1}{3}\)[/tex]:
[tex]\[ y - 1 = \frac{1}{3}(x - 1) \][/tex]
[tex]\[ y - 1 = \frac{1}{3}x - \frac{1}{3} \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{2}{3} \][/tex]
Multiplying by 3 to get the standard form:
[tex]\[ 3y = x + 2 \][/tex]
[tex]\[ x - 3y + 2 = 0 \][/tex]
2. For [tex]\(m_1 = -3\)[/tex]:
[tex]\[ y - 1 = -3(x - 1) \][/tex]
[tex]\[ y - 1 = -3x + 3 \][/tex]
[tex]\[ y = -3x + 4 \][/tex]
Multiplying by 1 to get the standard form:
[tex]\[ 3x + y - 4 = 0 \][/tex]
### Final Answer
The equations of the straight lines passing through the point of intersection of [tex]\(2x - 3y + 1 = 0\)[/tex] and [tex]\(x + y - 2 = 0\)[/tex] and making a [tex]\(45^\circ\)[/tex] angle with [tex]\(x + 2y - 5 = 0\)[/tex] are:
[tex]\[ x - 3y + 2 = 0 \][/tex]
[tex]\[ 3x + y - 4 = 0 \][/tex]
### Step 1: Find the Point of Intersection
First, we need to find the point of intersection of the lines [tex]\(2x - 3y + 1 = 0\)[/tex] and [tex]\(x + y - 2 = 0\)[/tex].
1. Solve the system of equations:
[tex]\[ x + y - 2 = 0 \][/tex]
[tex]\[ y = 2 - x \][/tex]
2. Substitute [tex]\( y = 2 - x \)[/tex] into [tex]\(2x - 3y + 1 = 0\)[/tex]:
[tex]\[ 2x - 3(2 - x) + 1 = 0 \][/tex]
[tex]\[ 2x - 6 + 3x + 1 = 0 \][/tex]
[tex]\[ 5x - 5 = 0 \][/tex]
[tex]\[ x = 1 \][/tex]
[tex]\[ y = 2 - 1 = 1 \][/tex]
Therefore, the point of intersection is [tex]\((1, 1)\)[/tex].
### Step 2: Determine the Slope of the Given Line
We need the slope of the line [tex]\(x + 2y - 5 = 0\)[/tex].
1. Rewrite the equation in slope-intercept form [tex]\(y = mx + c\)[/tex]:
[tex]\[ x + 2y - 5 = 0 \][/tex]
[tex]\[ 2y = -x + 5 \][/tex]
[tex]\[ y = -\frac{1}{2}x + \frac{5}{2} \][/tex]
Thus, the slope ([tex]\(m_2\)[/tex]) of the line [tex]\(x + 2y - 5 = 0\)[/tex] is [tex]\(-\frac{1}{2}\)[/tex].
### Step 3: Determine the Slopes of the Desired Lines
To find the lines making a [tex]\(45^\circ\)[/tex] angle with the slope [tex]\(m_2 = -\frac{1}{2}\)[/tex], we use the tangent formula for angles between two lines:
[tex]\[ \left| \frac{m_1 - m_2}{1 + m_1 m_2} \right| = \tan(45^\circ) = 1 \][/tex]
where [tex]\(m_1\)[/tex] is the slope of the desired line.
Substitute [tex]\(m_2 = -\frac{1}{2}\)[/tex]:
[tex]\[ \left| \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} \right| = 1 \][/tex]
This gives two cases:
[tex]\[ \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = 1 \][/tex]
[tex]\[ \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = -1 \][/tex]
Solve these equations separately:
1. First case ([tex]\( \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = 1 \)[/tex]):
[tex]\[ m_1 + \frac{1}{2} = 1 - \frac{1}{2}m_1 \][/tex]
[tex]\[ m_1 + \frac{1}{2}m_1 = 1 - \frac{1}{2} \][/tex]
[tex]\[ \frac{3}{2}m_1 = \frac{1}{2} \][/tex]
[tex]\[ m_1 = \frac{1}{3} \][/tex]
2. Second case ([tex]\( \frac{m_1 + \frac{1}{2}}{1 - \frac{1}{2}m_1} = -1 \)[/tex]):
[tex]\[ m_1 + \frac{1}{2} = - (1 - \frac{1}{2}m_1) \][/tex]
[tex]\[ m_1 + \frac{1}{2} = -1 + \frac{1}{2}m_1 \][/tex]
[tex]\[ m_1 - \frac{1}{2}m_1 = -1 - \frac{1}{2} \][/tex]
[tex]\[ \frac{1}{2}m_1 = -\frac{3}{2} \][/tex]
[tex]\[ m_1 = -3 \][/tex]
### Step 4: Equations of the Desired Lines
Using the point-slope form of the line equation, we can write the equations of the lines passing through [tex]\((1, 1)\)[/tex]:
1. For [tex]\(m_1 = \frac{1}{3}\)[/tex]:
[tex]\[ y - 1 = \frac{1}{3}(x - 1) \][/tex]
[tex]\[ y - 1 = \frac{1}{3}x - \frac{1}{3} \][/tex]
[tex]\[ y = \frac{1}{3}x + \frac{2}{3} \][/tex]
Multiplying by 3 to get the standard form:
[tex]\[ 3y = x + 2 \][/tex]
[tex]\[ x - 3y + 2 = 0 \][/tex]
2. For [tex]\(m_1 = -3\)[/tex]:
[tex]\[ y - 1 = -3(x - 1) \][/tex]
[tex]\[ y - 1 = -3x + 3 \][/tex]
[tex]\[ y = -3x + 4 \][/tex]
Multiplying by 1 to get the standard form:
[tex]\[ 3x + y - 4 = 0 \][/tex]
### Final Answer
The equations of the straight lines passing through the point of intersection of [tex]\(2x - 3y + 1 = 0\)[/tex] and [tex]\(x + y - 2 = 0\)[/tex] and making a [tex]\(45^\circ\)[/tex] angle with [tex]\(x + 2y - 5 = 0\)[/tex] are:
[tex]\[ x - 3y + 2 = 0 \][/tex]
[tex]\[ 3x + y - 4 = 0 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.